2008
DOI: 10.1016/j.ibmb.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lipid storage droplet protein-1 may define the role of AKH as a lipid mobilizing hormone in Manduca sexta

Abstract: Adipokinetic hormone (AKH) is the main hormone involved in the acute regulation of hemolymph lipid levels in several insects. In adult Manduca sexta AKH promotes a rapid phosphorylation of “Lipid storage protein-1”, Lsd1, and a concomitant activation of the rate of hydrolysis of triglycerides by the main fat body lipase. In contrast, in the larval stage AKH modulates hemolymph trehalose levels. The present study describes the sequence of a full length Lsd1 cDNA obtained from M. sexta fat body and investigates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…The concerted study of the three lipases, ATGL, TGL and HSL, and the role of the lipid droplet proteins, PLIN1 (Msex2.00753) and PLIN2 (Msex2.00753), previously named Lsd1 and Lsd2, should lead to advances in the biochemistry of lipid mobilization. PLIN proteins are lipid droplet resident proteins that play a major role in the regulation of storage of TG and DG production and secretion (Arrese et al, 2008a; Bi et al, 2012; Gronke et al, 2003; Patel et al, 2005; Teixeira et al, 2003). Studies in M. sexta demonstrated that AKH induces PKA-mediated phosphorylation of PLIN1 which activates the hydrolysis of TG (Arrese et al, 2008b; Patel et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The concerted study of the three lipases, ATGL, TGL and HSL, and the role of the lipid droplet proteins, PLIN1 (Msex2.00753) and PLIN2 (Msex2.00753), previously named Lsd1 and Lsd2, should lead to advances in the biochemistry of lipid mobilization. PLIN proteins are lipid droplet resident proteins that play a major role in the regulation of storage of TG and DG production and secretion (Arrese et al, 2008a; Bi et al, 2012; Gronke et al, 2003; Patel et al, 2005; Teixeira et al, 2003). Studies in M. sexta demonstrated that AKH induces PKA-mediated phosphorylation of PLIN1 which activates the hydrolysis of TG (Arrese et al, 2008b; Patel et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The total protein associated with purified LDs accounted for approximately 1.7% of total protein in the fat body homogenate. Lsd1, a protein that is found mostly associated with lipid droplets in Manduca sexta fat body (Arrese et al, 2008a), was used as fat body lipid droplet marker. As expected, the LDs fraction was enriched in this protein.…”
Section: Resultsmentioning
confidence: 99%
“…The higher abundance of Lsd1 in LDs from adult insects, as compared to LDs of larval fat body and ovaries, is consistent with the physiological state of adult insects, which are mobilizing FA from the fat body to the ovaries. Previous studies have linked the expression levels of Lsd1 (Arrese et al, 2008a) with the ability of M. sexta fat body to mobilize FA. Moreover, since adult insects are kept without food, they are also mobilizing and oxidizing FA to support basal metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Although these proteins are localized on the LD surface, they have both opposing and redundant functions (Bi et al, 2012). Lsd-1 modulates the accessibility of lipases, such as Drosophila hormone sensitive lipase (Hsl), to the LD and stabilizes the structure of the LD (Arrese et al, 2008;Beller et al, 2010). Lsd-1 mutant flies are hyperphagic and obese (Beller et al, 2010).…”
Section: Box 1 Lipid Droplet Proteinsmentioning
confidence: 99%